The impact of watching english cartoons on preschoolers’ language acquisition and behavioural development in Dhaka - Vijayaratnam, Phawani; Akhi, Mariam Khanum; Mohiuddin, Mohammad Golam; Zuraina, Ali; Manoochehrzadeh, Mehdi; Rajanthran, Subashini K. (Bilingual Publishing Group, 2025)
Being a critical development period, childhood shapes behaviors and language skills through interaction and observation. These days, the majority of the children spend a notable amount of time watching and enjoying English cartoons in Dhaka City. Watching cartoons has a significant impact on children in the development of their attitudes, actions, and skills. This study investigates the effects of watching English cartoons on preschoolers in Dhaka City. The study uses a triangulation method with a diverse sampling of 40 participants—20 preschoolers and 20 parents—combining questionnaires, semi-structured interviews of parents and children, and observation. To ensure the diversity of the sampling, we adopted convenience sampling and selected respondents from Dhaka City- North and South. The findings show that the impacts of watching English cartoons are both beneficial and concerning; children display impressive linguistic growth in English, particularly in applying lexis and understanding even complex contexts. On the other hand, exposure to violent content raises concerns about hazardous behavior and its imitation. We argue that it is important for parents to maintain national identity, cultural sensitivity, and awareness while letting children watch English cartoons. Parental monitoring is also necessary to select content that is in accordance with morals, educational activities, and critical thinking and to improve preschoolers’ education quality. We urge researchers to conduct further studies on the area to dive deeper into the facts.